2011
DOI: 10.5941/myco.2011.39.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and Plant Phenylalanine Ammonia-lyase

Abstract: L-Phenylalanine is one of the essential amino acids that cannot be synthesized in mammals in adequate amounts to meet the requirements for protein synthesis. Fungi and plants are able to synthesize phenylalanine via the shikimic acid pathway. L-Phenylalanine, derived from the shikimic acid pathway, is used directly for protein synthesis in plants or metabolized through the phenylpropanoid pathway. This phenylpropanoid metabolism leads to the biosynthesis of a wide array of phenylpropanoid secondary products. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 63 publications
6
128
2
6
Order By: Relevance
“…About 50 % of activity remained after incubation for 6 h at 60°C. Most plant PAL enzymes were considered to lose their activity as the temperature approached 60°C [27]. However, our results indicated that the ZmPAL2 was relatively stable at high temperatures.…”
Section: Biochemical Property Analysiscontrasting
confidence: 56%
“…About 50 % of activity remained after incubation for 6 h at 60°C. Most plant PAL enzymes were considered to lose their activity as the temperature approached 60°C [27]. However, our results indicated that the ZmPAL2 was relatively stable at high temperatures.…”
Section: Biochemical Property Analysiscontrasting
confidence: 56%
“…Fungal phenylpropanoid metabolism produces a wide range of secondary metabolites (Hyun et al 2011) in response to biotic or abiotic stresses including UV irradiation and interspecific competition for space and nutrients (Korkina 2007). These metabolites encompass diverse structural classes and biological functions (Lattanzio et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The phenylpropanoid pathway serves as a rich source of metabolites in plants, is required for the biosynthesis of lignin, and serves as a starting point for the production of many other important compounds involved in growth and development (Hyun et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites produced from the phenylpropanoid pathway include the cell wall structural polymer, lignin, flavonoids, UV protectants, wound protectants, isoflavonoid and furano coumarin phytoalexin antibiotics (Ozeki et al 2000;Ludwikow and Sadowski 2008;Hyun et al 2011).…”
Section: Introductionmentioning
confidence: 99%